La complessità della certificazione di Dipendenza da Sostanze Stupefacenti nel contesto penitenziario italiano: criticità e prospettive - Crespi, Giovanna; Varango, Concettina (Mission - Open Access, 2024)
In the Italian penitentiary system, the diagnosis of drug addiction represents a delicate intersection between medicine, law and prison management. This article seeks to examine the regulatory, clinical and practical challenges that infl uence the assessment and certifi cation of drug addiction.